2022
DOI: 10.3390/biology11071039
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental Habitats and Diets on the Gut Microbiota Diversity of True Bugs (Hemiptera: Heteroptera)

Abstract: Insects are generally associated with gut bacterial communities that benefit the hosts with respect to diet digestion, limiting resource supplementation, pathogen defense, and ecological niche expansion. Heteroptera (true bugs) represent one of the largest and most diverse insect lineages and comprise species consuming different diets and inhabiting various ecological niches, even including underwater. However, the bacterial symbiotic associations have been characterized for those basically restricted to herbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Here, our results of CCA and RDA emphasized the importance of phylogeny through the level of in uence of both. It was also demonstrated that a recent study con rmed that at the species level, the differences in gut bacterial diversity were mainly determined by diet and environmental habitats [53]. Therefore, we speculate that ecological factors may be the main determinants of intestinal bacterial diversity in the lower taxonomic levels, while species phylogeny may play a greater role in the higher taxonomic levels.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Here, our results of CCA and RDA emphasized the importance of phylogeny through the level of in uence of both. It was also demonstrated that a recent study con rmed that at the species level, the differences in gut bacterial diversity were mainly determined by diet and environmental habitats [53]. Therefore, we speculate that ecological factors may be the main determinants of intestinal bacterial diversity in the lower taxonomic levels, while species phylogeny may play a greater role in the higher taxonomic levels.…”
Section: Discussionmentioning
confidence: 51%
“…A recent study has illustrated that the gut microbes of domesticated animals are more diverse than those of wild animals [13]. Secondly, the gut bacteria of some herbivorous true bugs are more diverse than those of carnivorous true bugs [53]. Thirdly, the gut bacteria of herbivorous insects that feed on plant juices and wood are more diverse than those of natural herbivores [15,54].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data from six Harpactorini species, Li and colleagues suggested Enterococcus bacteria to be a conserved microbiome component to most assassin bugs (50). In our data, Enterococcus is however only found in some individuals of Reduvius sp.…”
Section: Microbiomes Of Related Predatory Assassin Bugsmentioning
confidence: 47%
“…Similarly to Triatoma, host species was a significant predictor of assassin bug microbiome alpha (Supplementary Table S1-DATASHEET S12) and beta diversity (Figure 2, Supplementary Table S1 2A). Species specificity and a single taxon dominance resemble the microbiome characteristics of related hematophagous kissing bugs (11) but pose a sharp contrast to the recently published microbiome patterns in Old World assassins (50).…”
Section: Microbiomes Of Related Predatory Assassin Bugsmentioning
confidence: 76%
See 1 more Smart Citation